Binary Synergy: AI-Driven Technology Adaptation, Scenario Implementation, and Value Reciprocity Between Digital Commerce and Cybersecurity (2025-2026) - Huang, Yu (International Journal of Multidisciplinary Research, 2026)
Artificial intelligence (AI) has forged an inseparable binary synergy between digital commerce and cybersecurity, operating through a three-layer bidirectional empowerment model: technology adaptation (tailoring AI capabilities to the unique needs of both domains), scenario implementation (deploying adapted AI tools to solve domain-specific and cross-domain challenges), and value reciprocity (converting implementation outcomes into mutual benefits that refine technology and expand scenarios). This review synthesizes 5 key studies (2025-2026) to unpack the synergy logic: technology adaptation lays the foundation by aligning modular AI architectures and privacy-enhancing technologies (PETs) with business inclusivity and cybersecurity risk balance; scenario implementation delivers practical solutions for SMB technical access, privacy-compliant marketing, and risk-cost optimized security management; value reciprocity amplifies synergy by using commercial growth to fund cybersecurity innovation and cybersecurity resilience to unlock business potential. Findings reveal that: the model operates as a bidirectional feedback loop—commerce-driven AI adaptation informs security tools, and security-focused implementation refines business AI; modularity and PETs are the core technical enablers; SMBs are the primary beneficiaries and catalysts of value reciprocity. This framework offers a targeted perspective on business-cybersecurity synergy, guiding researchers, practitioners, and policymakers to leverage AI for mutually reinforcing growth and resilience.